2020
DOI: 10.3390/jfb11040080
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Evaluation of the Stability of One or Two Miniscrews under Loading on Synthetic Bone

Abstract: The aim of the present study was to evaluate the primary stability of a two-miniscrew system inserted into a synthetic bone and to compare the system with the traditional one. Forty-five bi-layered polyurethane blocks were used to simulate maxillary cancellous and cortical bone densities. Samples were randomly assigned to three groups—one-miniscrew system (Group A, N = 23), two-miniscrew system (Group B, N = 22) and archwire-only (Group C, N = 10). A total of 67 new miniscrews were subdivided into Group A (23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…According to the study by Migliorati et al, by using the direct anchorage, the canine showed a 1 mm/month movement speed rate for the root apex and slightly faster movement in terms of cusp movement when compared to the use of the indirect [19,20]. The single-TAD approach is impressive and simple to handle, but it should be noted that some authors prefer the use of two-TAD technique to reduce any stability problems due to traction activation [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…According to the study by Migliorati et al, by using the direct anchorage, the canine showed a 1 mm/month movement speed rate for the root apex and slightly faster movement in terms of cusp movement when compared to the use of the indirect [19,20]. The single-TAD approach is impressive and simple to handle, but it should be noted that some authors prefer the use of two-TAD technique to reduce any stability problems due to traction activation [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of using the skeletal anchorage [ 10 ] to manage the agenesis is included in the consent form to avoid adverse dental effects and for the lack of dental anchorage in the anterior zone.…”
Section: Treatment Objectives and Alternativesmentioning
confidence: 99%
“…Taking into account the scientific literature, it was assumed that the microscrews were totally osseointegrated into the cortical blocks of the graft and the remaining bone of the jaw, considering the osseointegration to be the direct, structural and functional connection between the living bone and the surface of a microscrew [35][36][37]. Those areas not affecting the surgery are defined as fixed nodes and zero displacement was assumed for them [25,38].…”
Section: Properties Of Materialsmentioning
confidence: 99%